Design of A Successful Model for The Implementation of Blended Learning in Higher Education in Indonesia - Sihotang, Manorang; Aedah Abd Rahman; Hoga Saragih (Cita konsultindo, 2025)
The core objective of this study is to build a systematic evaluation framework to measure the success of blended learning in Indonesian universities. And at the same time, trying to offer a new model to measure the success factors of the implementation of blended learning by considering the perspectives of students and lecturers, which are ultimately expected to meet the needs of all stakeholders. The model developed in this research is the IPO logic model for combining 3 models, namely TRI, ACSR, and DeLone. In this study, researchers used quantitative data methods, with data collection techniques carried out by distributing questionnaires. Testing of 300 respondents, consisting of lecturers and students with Smart PLS 4.0, showed a degree of accuracy of the research measuring instrument used for the contents of the statement regarding the relationship between all factors measured. From the results of the second test, namely the reliability and validity test with Smart PLS 4.0 software on 300 data points, reliable and valid results were obtained. This study concludes that blended learning is an effective learning model in universities in Indonesia, with the success of implementation influenced by technological readiness, institutional support, and lecturer competence in managing online learning.